DEVELOPMENT OF DATA MESH DATA PLATFORM WITH ML DOMAIN OF DATA ANALYSIS - M. Fostyak; L. Demkiv (Електроніка та інформаційні технології, 2024)
A data mesh model with three input domains A, B, and C has been proposed. All domains have their own operational data source. Each domain team builds a data product for their domain, which includes only cleaned, processed, and selected data. The domain data products are then combined into a comprehensive aggregate containing all-encompassing data about the entities in the system. Next, consumer-aligned data products are created: a marketing data product, a company performance data product, and an ML data product. Thus, data mesh provides a decentralized and distributed data architecture for a project to deliver financial services to clients.